Learning Chest Imaging - Pedrozo Pupo, John C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Radiology of the thorax forms an indispensable element of the basic diagnostic process for many conditions and is of key importance in a variety of medical disciplines. This user-friendly book provides an overview of the imaging techniques used in chest radiology and presents numerous instructive case-based images with accompanying explanatory text. A wide range of clinical conditions and circumstances are covered with the aim of enabling the reader to confidently interpret chest images by correctly identifying structures of interest and the causes of abnormalities. This book, which will be an invaluable learning tool, forms part of the Learning Imaging series for medical students, residents, less experienced radiologists, and other medical staff. Learning Imaging is a unique case-based series for those in professional education in general and for physicians in prarticular.
Pleural and Pleural Space -- Diaphragm -- Mediastinum and Pulmonary Circulation -- Air Space, and Bronchi I -- Air Space, and Bronchi II -- Trachea and Airway -- Heart and Great Vessels -- Chest Wall and Soft Tissues -- Pulmonary Interstitium -- Medical Device, and Monitoring of the Chest.
Keywords: Medicine; Radiology, Medical; Pneumology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Pneumology/Respiratory System